Ready for transition: understanding the experiences of student-athletes’ participation in intercollegiate sports - Gayatgay, Noe; Longakit, Jet C.; Asuncion, Sasha Blanche; Aliser, Johnlenon (Edu Sportivo: Indonesian Journal of Physical Education, 2024)
Background: Various studies have examined the transitional experiences of student-athletes from specific sports; however, there is a scant amount of literature analysing how student-athletes dealt with the transition from high school to intercollegiate sports participation in the Philippine context. Research Objective: This study aims to examine the transition of student-athletes from high school to intercollegiate sports participation. Methods: This study explored the beneficial experiences of six athletes at the MSU-Iligan Institute of Technology in the transition from high school to intercollegiate sports participation. The study used an explanatory, descriptive qualitative design with data obtained through semi-structured interviews. Finding/Result: The results of the study found challenges in managing the transition: focus and commitment, and the coach-athlete relationship. Additionally, this study has identified a support system that has had a significant impact on their overall athletic performance: it increases motivation and boosts morale. The study found the differences between the transitions in terms of training, dealing with coaches, and working with fellow athletes; the effect of the transition on the overall performance of student-athletes; the support system from different people and organisations; and the impact of the support system on the arrangements of student-athletes. The study’s results emphasise the importance of support systems in mitigating the challenges experienced in the transition from high school to intercollegiate sports participation. Conclusion: These findings suggest that the transition and support systems have a substantial influence on the development of athletes. The findings showed that the participants exhibited a preference for prioritising their academic pursuits over attempting to balance academic and sports careers. This study provides quality results that could help the university develop its sports programme.